Structural Analysis of Polyhedral Oligomeric Silsesquioxane Coated SiC Nanoparticles and Their Applications in Thermoset Polymers. (7th December 2015) - Reza-E-Rabby, Md.; Jeelani, Shaik; Rangari, Vijaya K.
Abstract : The SiC nanoparticles (NPs) were sonochemically coated with OctaIsobutyl (OI) polyhedral oligomeric silsesquioxane (POSS) to create a compatible interface between particle and thermoset polymer. X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) techniques were used to analyze the structure of OI-POSS coated SiC nanoparticles. These results revealed the formation of a covalent bonding between SiC and OI-POSS. The transmission electron microscopy (TEM) analysis of OI-POSS coated SiC nanoparticles has also shown the indication of attachment between these two nanoparticles. The OI-POSS coated SiC nanoparticles were further reinforced into a thermoset resin system in order to evaluate mechanical and thermal properties of nanocomposites. The flexural strength, modulus, and glass transition temperature were found to be enhanced while SiC and OI-POSS coated SiC were infused into epoxy system compared to those properties of neat epoxy resin.